(untitled) (Global Business Management Review (GBMR), 2019)
Michael (General Manager) is having a weekly meeting with the team, the overall production process and flow are running smooth and in an orderly manner. When Sam (Factory Manager) informs Michael that few orders received unable to fulfil within the stipulated time monthly. Michael stunned with this none achieving number and worrying this rate is getting up. Ultimately, the company’s objectives are to provide excellent customer experience and maximizing the shareholders’ wealth will be impacted. He needs to find out the best solution to handle this none fulfilment of the order, interruption on the production processes, customer dissatisfaction or sourcing alternative suppliers, increase in the production cost and unforeseen impact on the total business. He does concern the existing 34 production lines need to be rearranged the layout, machines prioritization and output maximization, manpower allocation and commissioning. He needs to plan this well before the next meet up with the board of directors. Rubber product business is very competitive and high demanding locally and internationally. The company overseas orders (e.g. Europe, Southeast Asia, and Australasia) keep increasing from month to month. New customers are foreseen to be coming in (at 5% incremental by monthly) with referring to the previous year records. In 2005, the company has obtained ISO 9001:2000 certified by SIRIM QAS international. Eventually, the manufacturing and quality assurance procedures are certified by the ISO 9001:2008 Quality Management System. He shall make sure an excellent customer experience and maximization of the shareholders’ wealth is achieved.